Chapter Jernej Kopitar nella cultura slovena - Mitrovic, Marija (Biblioteca di Studi Slavistici, 2019)
According to 19th-century philologist Jernej Kopitar, elite literary traditions and modern written languages originated in folk literature. Leading Slovenian intellectuals of his day, however, including poet France Prešeren and linguist and critic Matija Čop, favored classic poetic forms reminiscent of the Italian Renaissance. In Slovenian literary history, Kopitar has remained a figure of secondary importance; nonetheless, his role in other South Slavic cultures was preeminent. We examine several attempts to revert this tendency and to ascribe to Kopitar, and not only to Čop, a leading role in Slovenian nation-building.